A Low Complexity Dual-Phase Alternating Scheme is Used With the PTS Method to Reduce PAPR for B5G Systems - Yung-Ping Tu; Chen-Wei Hsu (IEEE Access)
In this paper, we investigate the peak-to-average power ratio (PAPR) issue in orthogonal frequency division multiplexing (OFDM) and beyond fifth-generation (B5G) systems. To deal with this problem, we propose an efficient two-stage scheme to alleviate PAPR obsession in OFDM, F-OFDM, and UFMC waveforms, named dual-phase alternating partial transmission sequence (DPA-PTS). In the first stage, we use the partial transmission sequence (PTS) scheme to produce an acceptable PAPR threshold, which can be used as the initial upper bound level for the second stage. To reduce computational complexity, before entering the second stage, we employ the pre-process by Monte Carlo method to estimate the amount of subcarriers worth altering, denoted as $β $ . In the second stage, we use the dual-phase alternation of 0 and $π $ radian to wimple the effect of the peaking power of each subcarrier on PAPR one by one until the estimated amount $β $ . It can significantly reduce the computational complexity due to only being made in the simple amplitude phase-reverse operation for maximum $β $ critical amended subcarriers. Simulation results show that the proposed scheme achieves better PAPR performance and computational complexity regardless of the waveform than previous well-known techniques, such as PTS, selective mapping (SLM), etc. In the UFMC example, when the complementary cumulative distribution function (CCDF) is $10^{-4}$ , compared with the original waveform, the PTS scheme, and the SLM scheme, the PAPR performance of the proposed scheme is improved by about 2.74, 1.87, and 0.35 dB respectively. Of course, our proposed method’s bit error rate (BER) consistently outperforms the original waveform due to a valid PAPR reduction that weakens nonlinear distortion from the power amplifier.